Community Participation-Based Disaster Education Model: An Empirical Analysis of Disaster Hazards in Demak Regency, Indonesia - Nur Hamid; Inero Valbuena Ancho; Hanifah Mahat; Dina Ruslanjari; Juhadi Juhadi (Jurnal Mamangan, 2025)
This study addresses the issue of disaster vulnerability in Demak Regency, an area highly exposedto tidal flooding, coastal erosion, and extreme weather. The objective of the research is toformulate a community participation-based disaster education model that strengthenspreparedness and resilience at the local level. Theoretically, the study draws on disaster riskreduction frameworks emphasizing community empowerment, participatory education, andintegration of local wisdom. A mixed-methods approach was employed, combining quantitativeZ-score analysis of disaster data from 2020–2022 with qualitative thematic analysis using NVivoto assess literature, policy documents, and community practices. The results reveal that disasterhazards in Demak are spatially varied: Sayung District is categorized as high-hazard, Guntur asmedium, while twelve other sub-districts fall into the low category. These findings highlight thenecessity of contextualized disaster education tailored to specific local hazards. The proposedmodel integrates schools, communities, and cultural traditions to enhance disaster literacy, fostersocial cohesion, and improve adaptive capacity. The conclusion emphasizes that a participatory,location-specific education framework is more effective than uniform approaches and can bereplicated in other disaster-prone regions. The novelty of this study lies in combining empiricalhazard mapping with community participation principles to design a disaster education modelthat is both data-driven and socially embedded, thereby bridging gaps between statistical riskassessment and local educational practice.